TRAINING FOR THE DEVELOPMENT OF LITERATURE TEACHING MATERIALS FOR INDONESIAN TEACHERS AT SMP LEVEL IN THE REGION OF EAST ACEH DISTRICT - Joko Hariadi; Muhammad Taufik Hidayat; Mauliza Mauliza (Global Science Society, 2022)
In this community service activity, the PKM Team of Unsam simplified Borg and Gall's development from 9 to 3 stages, namely dedication and information gathering, planning for making teaching materials for reading literature, and product development. The results of the service resulted in contextual-based literature reading teaching materials for junior high school Indonesian language teachers in the East Aceh district. This module consists of three parts. The first part is the presentation of the outer cover, preface, presentation of SK and KD, introduction, table of contents, and review of literature reading. The second part is in the form of content based on SK and KD, namely identifying the intrinsic elements of drama texts, making a youth novel synopsis, explaining the plot, actors, and setting of the novel, and recognizing general characteristics of poetry from poetry anthology books, and at the end of the lesson a formative test is included. and self evaluation. The third part of the presentation of this book consists of a glossary, answer keys and bibliography. The validation results of teaching materials from material experts, Indonesian language teachers, and students show: (1) the content feasibility aspect is in the "good" category; (2) aspects of language and images are in the "good" category; (3) "good" presentation aspect; and (4) "good" graphical aspects.